Systematic Literature Review (SLR): Analisis Keterampilam Membaca Melalui Legenda Asal – Usul Kota Kudus pada Siswa Sekolah Dasar - Tsabita Hanun Mumtaza P; Anka Putri Cahyaningtias; Marwah Azzahra Diani; Luthfa Nugraheni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the effectiveness of using the local legend “The Origins of Kudus City” as a learning medium to improve reading skills in elementary school students. This legend was chosen for its three unique features: first, it contains the historical narrative of Sunan Kudus, rich in Islamic-Javanese acculturation values; second, it has strong geographical relevance to students’ daily lives in Kudus; third, it presents potential for character visualization and cultural settings that are engaging for early-age readers. The study aims to analyze the influence of local legends on students’ reading development. A Systematic Literature Review (SLR) was conducted by analyzing seven relevant articles sourced from academic databases such as Google Scholar, DOAJ, and Scopus. The inclusion criteria focused on reading skills, elementary school students, learning media, and the legend of Kudus City. The results indicate that illustrated storybooks based on local legends can significantly enhance reading comprehension, increase student motivation, and encourage active classroom participation. Additionally, this learning media enables the integration of local cultural values into the educational process, making learning more contextual and meaningful. Thus, illustrated storybooks based on the legend of “The Origins of Kudus City” are proven effective as an innovative learning tool that not only strengthens reading skills but also preserves local wisdom in elementary education.